‘Hyped up’: Assemblages of alcohol, excitement and violence for outer-suburban young adults in the inner-city at night - MacLean, S.; Moore, David (Elsevier BV, 2014)
Background: Young adults from across greater Melbourne are drawn to the city centre night time economy (NTE). There is some evidence that young adults who live in outer-suburbs are involved in higher rates of weekend night time assaults than their inner-urban peers, both as perpetrators and as victims. Using the notion of ‘assemblages’, this article explores outer-suburban people’s participation in the affectively charged spaces of inner-city entertainment precincts to show that trouble in the NTE cannot be attributed to alcohol and other drugs alone.Methods: We provide a narrative analysis of interviews conducted in 2012 with 60 young adult drinkers aged 18–24, half of whom lived in an inner-city area and half in outer-suburbs.Results: More so for young adults from outer-suburbs than those who live closer to the city, going tothe city is an event marked out as different from everyday life. Their sense of being ‘hyped up’ in the inner-city made different sets of practices possible, particularly in relation to drinking and being open to new engagements with friends and sexual partners. Participants also spoke, however, of discomfort, danger and fear. Violence was most likely to occur at points where people felt a dissonance between their heightened affective states and the spaces where they found themselves.Conclusion: In this analysis, outer-suburban young adults’ positioning within the assemblages of thecity centre NTE makes conflict and violence more likely for them. Efforts to improve NTE safety should maintain a focus on managing alcohol availability. Nonetheless additional strategies to decentralise the NTE, ensure better late night public transport to outer-suburbs or to support people to manage sudden affective shifts in NTE might also play a greater part in the overall effort.